Hydrogen: A sustainable fuel for future of the transport sector. (November 2015) - Singh, Sonal; Jain, Shikha; PS, Venkateswaran; Tiwari, Avanish K.; Nouni, Mansa R.; Pandey, Jitendra K.; Goel, Sanket
Abstract: Mobility (transport of people and goods) is a socio-economic reality and need for which is bound to grow in the coming years. Modes of transport should be safe, economic and reasonably environmental friendly. Hydrogen could be ideal as a synthetic energy carrier for transport sector as its gravimetric energy density is very high, abundantly available in combined form on the earth and its oxidation product (water) does not contribute to greenhouse gas emissions. However, its sustainable production from renewable resources economically, on-board storage to provide desirable driving range, usage in durable energy conversion devices and development of infrastructure for its delivery remain significant challenges. In this article, recent developments in the field of production, storage, transport and delivery of hydrogen along with environmental and safety aspects of its use as an energy carrier are presented. Almost any energy source can be used to produce hydrogen. Presently, non-renewable sources dominate hydrogen production processes but the need of the hour is to develop and promote the share of renewable sources for hydrogen production to make it completely sustainable. Hydrogen may be used as fuel for almost any application, where fossil fuels are used presently and would offer immediate benefits over the conventional fuels, if produced from renewable sources. For achieving a successful "hydrogen economy" in the near future, the technical and economic challenges associated with hydrogen must be addressed quickly. Finding feasible solutions to different challenges may take some time but technological breakthrough by way of on-going efforts do promise hydrogen as the ultimate solution for meeting our future energy needs for the transport sector.